Skyrme RPA description of γ-vibrational states in rare-earth nuclei - Nesterenko, V. O.; Kartavenko, V. G.; Kleinig, W.; Kvasil, J.; Repko, A.; Jolos, R. V.; Reinhard, Paul-Gerhard (EPJ Web of Conferences, 2016)
The lowest γ-vibrational states with Kπ = 2+γ in well-deformed Dy, Er and Yb isotopes are investigated within the self-consistent separable quasiparticle random-phase-approximation (QRPA) approach based on the Skyrme functional. The energies Eγ and reduced transition probabilities B(E2)γ of the states are calculated with the Skyrme force SV-mas10. We demonstrate the strong effect of the pairing blocking on the energies of γ-vibrational states. It is also shown that collectivity of γ-vibrational states is strictly determined by keeping the Nilsson selection rules in the corresponding lowest 2qp configurations.
CRIS-Team Scopus Importer:2023-07-24